Receptores EP1 E EP3 modulam as crises epilépticas induzidas por pentilenotetrazol e ácido caínico em camundongos - Banderó, Cristina Ruedell Reschke (2013)
Epilepsy is one of the most common neurologic disorders. It has been suggested that seizures may be facilitaded by inflammation. PGE2 is one of the most important inflammatory mediators, and facilitates pentylenetetrazol (PTZ)-induced seizures by stimulating EP1 and EP3 receptors. However, up to the present moment, no study has investigated whether EP1 and EP3 receptors blocking attenuate seizures induced by convulsants other than PTZ. It is also unknown whether Na+,K+-ATPase activity alterations are involved in such an effect. Therefore, in the current study we investigated whether EP1 and EP3 ligands (agonists and antagonists) modulate PTZ- and kainic acid (KA)-induced seizures, and whether alterations in Na+,K+-ATPase activity mediate such a protective effect, in mice. EP1 and EP3 antagonists (ONO-8713 and ONO-AE3-240, respectively, 10 Og/kg, s.c.) attenuated PTZ (60 mg/kg, i.p.)- and KA (20 mg/kg, i.p.)-induced seizures. The respective agonists (ONO-DI-004 and ONO-AE-248, 10 Og/kg, s.c.) facilitated seizures in both acute models, and at noneffective doses, prevented the protective effects of the antagonists. Animals injected with PTZ presented decreased Na+,K+-ATPase activity in the cerebral cortex and hippocampus. On the other hand, animals injected with KA presented increased Na+,K+-ATPase activity in the same cerebral structures at the end of the experiment. These divergent findings suggest that alterations in Na+,K+-ATPase activity in both acute models depends on the convulsant agent used and make difficult to establish a relationship between Na+,K+-ATPase activity and seizure development. Moreover, EP1 and EP3 antagonists administration abolished Na+,K+- ATPase activity alterations induced by PTZ and KA, in such a way that these alterations seem to be related more to the presence of ictal phenomenon itself than to the seizure induction mechanisms. Notwithstanding, the currrent results clearly show that EP1 and EP3 receptors might constitute novel targets for anticonvulsants development, since EP1 and EP3 decreased seizures, regardless of the convulsant agent used.